Role of Emotional Intelligence on Employee Performance in Selected Public Sector Banks in Madhya Pradesh State (Jabalpur Region) - Shivani Tiwari (Journal of Corporate Finance Management and Banking System, 2024)
In the wake of a seemingly rigorous recruitment process in the banking industry, where candidates' intelligence level appears to be more important than their emotional state, this study investigated how employees' emotional intelligence is related with job performance in selected banks in Madhya Pradesh state. Emotional intelligence was categorized by empathy, while employee performance was categorized by employee turnover. This study used a correlational research design. Three banks from the state of Madhya Pradesh have been selected for coverage. Pearson's Product Moment Correlation Coefficient was used for data analysis. The results revealed that empathy has a strong negative relationship with employee turnover. It is recommended that management implement policies that both ensure the employment of emotionally intelligent employees and create opportunities within the organization that improve employee relations and employee performance to reduce employee turnover.